Kecerdasan Emosional dan Adversity Quotient ditinjau dari Kemampuan Pemecahan Masalah Matematis Siswa - Nurul Bayyinah; Retno Subekti (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
Problem-solving skills play an essential role in learning mathematics. Having good problem-solving skills will help students to learn mathematics more effectively. These skills depend not only on cognitive abilities but are also significantly influenced by affective factors such as emotional intelligence and adversity quotient. This study aims to systematically investigate the relationship between emotional intelligence and adversity quotient concerning students' mathematical problem-solving. This research method is a literature review that collects research from the last ten years to be compiled, analyzed, and concluded, which involves reviewing various references and relevant research findings to obtain a theoretical basis for this research. The results of the study show that emotional intelligence and adversity quotient have a direct impact on students' mathematical problem-solving skills. Emotional intelligence strongly influenced students' ability to deal with complex mathematical challenges, while the adversity quotient contributed to persistence and resilience in problem-solving. This study found that students with higher emotional intelligence and adversity quotient tended to use more effective strategies in solving mathematical problems. The results can be used as a phenomenon and basis for improving mathematical problem-solving skills that consider students' emotional intelligence and adversity quotient.